The Role of Social Capital with Local Wisdom in Household Food Security in Bali Province - Purwanti, Putu Ayu Pramitha; Saskara, IdaAyu Nyoman (Jurnal Ekonomi Kuantitatif Terapan; 2022: Vol. 15, No. 1, Februari 2022 (pp.1-161)DO - 10.24843/JEKT.2022.v15.i01.p10, 2022)
Despite the fact that Bali Province has an excellent level of food security, it does not necessarily mean that all individuals in the region have equal accesses to food. Considerable challenges may arise from both supply and demand sides. The objectives of this research are to identify the effect of social capital on household food security in Bali Province and to examine the various forms of social capital with local wisdom that affect household food security in Bali Province. This research uses primary data collected under the purposive nonrandom sampling method. The research objectives were achieved by employing multiple linear regression analyses. The analysis variable is social capital as variable of interest while also taking into consideration several control variables in forms of individual characteristics and household characteristics. The results show that social capital has an effect on food security as an indicator of household welfare. The identification of social capital with local wisdom of households in Bali Province serves as a reference for alternative approaches in achieving food security in Bali Province.